2018
DOI: 10.3390/s18124086
|View full text |Cite
|
Sign up to set email alerts
|

Cold Plasma as an Innovative Construction Method of Voltammetric Biosensor Based on Laccase

Abstract: Development of new, faster methods of biosensor construction is a huge challenge for current science and industry. In this work, biosensor construction was carried out using a new soft plasma polymerization (SPP) method in which a bio-recognition layer of laccase enzyme was polymerized and bonded to a glassy carbon electrode (GCE) substrate under atmospheric pressure with a corona discharge jet. Laccase belongs to the oxidoreductase enzyme group with four copper atoms in its active center. Application of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…Characterization of the Plasma Discharge. The current and voltage measurements were consistent with previous descriptions of nonthermal helium plasma discharges at atmospheric pressure [24,27]. As shown in Figure 3, the applied power was provided as a pulsed discharge with a damped pseudo-sinusoidal wave form.…”
Section: Resultssupporting
confidence: 87%
“…Characterization of the Plasma Discharge. The current and voltage measurements were consistent with previous descriptions of nonthermal helium plasma discharges at atmospheric pressure [24,27]. As shown in Figure 3, the applied power was provided as a pulsed discharge with a damped pseudo-sinusoidal wave form.…”
Section: Resultssupporting
confidence: 87%
“…On the other hand, the available literature on the study of the effects of plasma treatments on polymers is rather large. For instance, studies on the modification of the surface properties of polymeric materials in several fields have been performed employing dielectric barrier discharges, plasma jets, glow discharges [23,24,25,26,27,28,29,30,31,32,33], and plasma polymerization [34,35,36]. Despite this, the operating conditions (discharge power, pressure, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…The research in this field has received renewed impetus in recent years due to the development of atmospheric pressure (AP) plasma technology, which represents nowadays a new avenue for surface processing of materials with reduced costs and easy-to-handle apparatuses, even under open air conditions [27][28][29][30][31][32][33][34][35]. Novel strategies have been proposed for enzyme immobilization.…”
Section: Introductionmentioning
confidence: 99%
“…It has been also demonstrated that, due to their remote operation, atmospheric pressure plasma jets offer a unique tool towards enzyme immobilization under soft reactive conditions [33]. Indeed, they can afford the desired surface modification with easier, faster, and more cost-effective plasma processes [27,[32][33][34]. Moreover, considerable efforts have been devoted to investigate the direct interaction of AP non-equilibrium plasmas with various biomolecules (e.g., proteins and nucleic acids) both in the dry state and in aqueous solutions, focusing on many different biomedical, biotechnological, and pharmaceutical applications [28,[35][36][37][38][39][40][41][42][43][44][45].…”
Section: Introductionmentioning
confidence: 99%